The correlation between HLA class II and β-thalassemia major in Al-Karama teaching hospital - Zeiny, Sarmad M. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Thalassemia is a form of inherited autosomal recessive blood disorder characterized by abnormal formation of hemoglobin.Objective: Determine frequencies & association of HLA class II alleles (DRB1& DQB1) in Iraqi β-thalassemia major patients.Patients: seventy unrelated randomly selected β-thalassemia major patients, and one hundred unrelated randomly selected healthy individuals, composed the control group.Methods: low resolution PCR-SSO (Sequence Specific Oligonucleotide) technique was used for HLA typing.Results: HLA DQB1*5 give significance importance as an etiological risk factor for β-thalassemia major; HLA DQB1*3 give significance importance as a preventive risk factor for β-thalassemia major.Conclusion: The positive association of HLA DQB1*5 and DQB1*3 with β-thalassemia major may have the possibility that these antigens, or the genes encoding them, are closely linked with other possible susceptibility genes.